Investigation on characteristics and origin of ferromagnetic dust in EAST - Hongyan Pan; Rong Yan; Rui Ding; Lei Mu; Jianlong Chai; Wei Zheng; Yuming Liu; Baoguo Wang; Yuxian Wen; Dahuan Zhu; Junling Chen (Nuclear Fusion)
Dust is one of the most critical issues in next-generation magnetic fusion devices, as it is inevitable and poses a serious threat to machine operation and safety. In EAST, a total of 7.82 g dust from the vacuum vessel and 5.81 g from the lower port K were collected and characterized after the 2021 first experimental campaign. The strong, weak and non-magnetic dusts were categorized using permanent magnets with surface magnetic field intensities of 50 mT and 500 mT. The distribution, morphology, and composition of different magnetic dust were found to be quite different. The dust obtained in the vacuum vessel contained a substantial amount of non-magnetic particles, exceeding 55 wt.% (weight percentage). In contrast, the lower port K predominantly consisted of strong magnetic dust, up to 60.1 wt.%. The non-magnetic dust exhibited broken spheroidal particles and needle-like particles, primarily composed of Li _2 CO _3 and carbon. Both the strong and weak magnetic dust have a similar content of stainless steel (SS)-based elements but different morphology. The strong magnetic dust are mainly spheroids, formed by solidification after the melting of the SS materials. These spheroidal particles were found to agglomerate with four distinct types of grains: equiaxed grains, dendritic, cellular dendritic and spherulite grains due to the different temperature gradients during solidification. The spheroidal particles in the strong magnetic dust have an oxygen content of around 26.6 wt.%, which are much different from the weakly magnetic dust with a much lower oxygen content of 3.9 wt.% and in strip-like formations. Furthermore, the strong magnetic dust was found to be a type of ferromagnetic material, predominantly with 46.4 wt.% content of a new phase of γ -Fe _2 O _3 . It could be activated in the presence of a magnetic field inside the EAST tokamak, which elucidates the higher concentration of strongly magnetic dust in the lower port K. It could have an impact on plasma start-up and impurity levels during plasma operation.